2012
DOI: 10.1248/bpb.35.127
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Administration of Cardanol (Ginkgol) Extracted from Ginkgo biloba Leaves and Cashew Nutshell Liquid Improves Working Memory-Related Learning in Rats

Abstract: Cardanol (ginkgol) extracted from Ginkgo biloba leaves and cashew nutshell liquid enhances the growth of NSC-34 immortalized motor neuron-like cells and, when chronically administered to young rats, improves working memory-related learning ability as assessed by eight-arm radial maze tasks. These findings suggest that cardanol is one of the components in Ginkgo biloba leaves that improves cognitive learning ability.Key words Ginkgo biloba; Anacardium occidentale; cardanol; motor neuron-like cell; working memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…generates an inflammatory process characterized by leukocyte aggregation and fluid extravasation; with participation of cytokines, nitric oxide, leukotrienes, and PGE2 [44]. Our data suggest that 2-AP reduces carrageenan-induced leukocyte migration as well as eugenol and estragole, both phenylpropanoids which have been shown to reduce chemotactic-stimulated cell migration [12, 48].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…generates an inflammatory process characterized by leukocyte aggregation and fluid extravasation; with participation of cytokines, nitric oxide, leukotrienes, and PGE2 [44]. Our data suggest that 2-AP reduces carrageenan-induced leukocyte migration as well as eugenol and estragole, both phenylpropanoids which have been shown to reduce chemotactic-stimulated cell migration [12, 48].…”
Section: Discussionmentioning
confidence: 87%
“…Its essential oil (EO) presents antioxidant efficacy in both in vitro and in vivo studies [9]. Previous research, involving GB essential oil, identified 68 compounds; one was cardanol, a bioactive compound already described in the literature for having antimicrobial, antioxidant, antitumor, and antifungal activity and improving cognitive ability and learning [10–12].…”
Section: Introductionmentioning
confidence: 99%
“…These results show that especially (+)-dihydroquercetin ( 1 ) and (−)-secoisolariciresinol ( 2 ) enhance neurite outgrowth more actively than the previously described cardanol and curcuminoids, which are only active in the micromolar range and achieved maximal stimulation of neurite outgrowth by 2-fold. For instance, Tobinaga et al showed that cardanol (ginkgol) extracted from Ginkgo biloba leaves enhanced the growth of NSC-34 immortalized motoneuron-like cells (1.4-fold) and improved working memory-related learning in rats when administered chronically. Moreover, certain curcuminoids were shown to promote neurite outgrowth in PC12 cells at micromolar concentrations, and the total neurite length was increased by 1.4- to 2.2-fold…”
Section: Resultsmentioning
confidence: 99%
“…Cytotoxicity often depends on a dosage several times the threshold effective dose of the anesthetic for a certain duration during exposure. At the same time, some drugs such as L-theanine, the coumarin derivative and ginkgol can improve the damage of inhaled anesthetics to NSCs and improve subsequent cognitive impairment (Chen et al, 2020;Kong et al, 2015;Tobinaga et al, 2012).…”
Section: Discussionmentioning
confidence: 99%